Calvatia Lilacina Extracts Exert Anti-Breast-Cancer Bioactivity through the Apoptosis Induction Dependent on Mitochondrial Reactive Oxygen Species and Caspase Activation. (24th March 2022) - Zeng, Qinghua; Singh, Ragini; Ye, Yong; Cheng, Shuang; Fan, Chen; Zeng, Qingmei
Abstract: Puffballs are a class of fungi widely distributed worldwide and associated with various bioactivities. This research mainly showed the antitumor bioactivity of extracts from Calvatia lilacina (CL), which is a common variety of puffballs. NMR and high-performance liquid chromatography methods are used to characterize the extracts. Results showed that CL extracts obtained with petroleum ether, ethyl acetate, ethanol, and water elicited obvious inhibitory effects on the proliferation of A549, Caco-2, and MDA-MB-231. Among these extracts, petroleum ether extract demonstrated the highest performance. This extract was then separated into seven sub-fractions (SFs). Three of these SFs (3#, 6#, and 7#) induces a decrease in the viability of MDA-MB-231 cells in which 7# SF exhibited the highest cytotoxicity, where the major component was found to be ergosta-7, 22-dien-3-one. Further tests revealed that 7# SF from petroleum ether extract could trigger severe cell death in human breast cancer cells (MDA-MB-231) by activating the apoptotic pathway dependent on mitochondrial reactive oxygen species and caspase activation. All these results in combination indicate that the mechanism of extract-potentiated apoptosis associates closely with ROS-dependent mitochondrial dysfunction events which further induces mitochondria-mediated intrinsic cytochrome C-caspase-related pathway of apoptosis. Supplemental data for this article is available online at https://doi.org/10.1080/01635581.2021.1936576